TERMINOLOGI KORUPSI MENURUT PERSPEKTIF HUKUM PIDANA ISLAM - Syarbaini, Ahmad (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2024)
Corruption comes from the Latin coruptio and corruptus which means to bribe and corrumpere which means to destroy. Corruption is included in jarîmah. Jarîmah is: "Prohibitions of syara', namely; Threats with 'uqūbat had or ta'zir". Ta'zir is: "'uqūbat determined by the authorities in order to refuse thinning and prevent crime". Terminology of Corruption in Indonesian law is: "Unlawfully committing acts of enriching oneself or another person or a corporation that can harm state finances or the state economy". While the terms that are close to corruption in Islamic studies are: "ghulūl, ikhtilâs, risywah and al-fasad and". Corruption according to fiqh is: "It is a jarîmah or a modern and extraordinary crime for which there is no agreement on the terms and definitions. While the 'uqūbat is ta'zîr which is returned to waliyul amri".